Influence of Si in maize plants in Kenyan populations of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Nuambote-Yobila, Ovide; Musyoka, Boaz; Njuguna, Elijah; Bruce, Anani Yaovi; Khamis, Fathia M.; Subramanian, Sevgan; Marion-Poll, Frédéric; Calatayud, Paul-André (Springer, 2022)
The fall armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae), native to the Americas, was confirmed in West and Central Africa in 2016 and reported in almost all countries of sub-Saharan Africa in 2017, becoming thereafter one of the major constraints on the production of maize, the main staple food crop in the region. Cereals depend on silicon (Si)-based defences to fight off herbivores. Both FAW strains, namely rice and corn strains, have been found to be present in Kenya. The present study tested the influence of Si on larval survival and relative growth rate according to the FAW strain, using potted maize plants treated with 10 and 20 g of Si. The results showed that plants treated with Si disturbed the larval growth of FAW larvae only from the corn strain but not from the rice strain. Overall, the corn strain performed better on maize as compared to the rice strain regardless of Si treatment, explaining why it has become the most abundant strain in Africa.